IMPLEMENTASI METODE COOPERATIVE LEARNING DALAM MEMBINA KEMAMPUAN MEMBACA AL-QUR’AN SISWA DI SMK NEGERI 03 PEKALONGAN - Prayogi, Arditya; Fiani, Qorina (Prodi Pendidikan Agama Islam STAIN Mandailing Natal, 2023)
This article describes how the implementation of the cooperative learning method in fostering students' Al-Qur'an reading skills at SMK Negeri 03 Pekalongan. This is because the cooperative learning method is one of the methods that can be applied in learning the Qur'an. The cooperative learning method itself is proven to be able to improve students' ability to understand the material or lessons that have been given and to be able to solve problems collectively. This article was written using a qualitative approach with a type of field research. Data collection techniques used include observation, interviews, and documentation. The data analysis uses data reduction, presentation and conclusion. The results of the study show that the students' ability to read the Qur'an is quite good. PAI teachers at SMK Negeri 03 Pekalongan can foster students' ability to read the Koran through the implementation of the cooperative learning method which has three stages, namely the planning stage, the implementation stage, and the closing stage. However, in its application there are several obstacles, including attitudes, and obstacles in preparation or maturity in preparing the results of the discussion. As a solution to this problem, several efforts were made, namely forming appropriate and efficient groups and preparing the things needed when learning was carried out.